Transcription analysis of TIMP-1 and NM23-h1 genes in glioma cell invasion Análise transcricional dos genes TIMP-1 e NM23-H1 na invasão celular em astrocitoma difuso e glioblastoma multiforme - José Augusto Nasser; Asdrúbal Falavigna; Fernando Ferraz; Gregory Duigou; Jeffrey Bruce (Arquivos de Neuro-Psiquiatria)
PURPOSE: To evaluate using transcription analysis the presence and importance of two genes: NM23-H1 and TIMP-1 on control of tumor cell invasion in diffuse astrocytomas (WHO II) and glioblastoma multiforme (WHO IV). METHOD: Northern blot analysis of NM23-H1 and TIMP-1 was performed. Eight diffuse astrocytomas and 19 glioblastomas (WHO IV) were analyzed to determine if TIMP-1 and NM23-H1 were candidates to inhibition of tumor cell invasion quantitated RNA levels. The samples were collected directly from operating room. Total cellular RNA was extracted from frozen tissue samples using guanidinium-isothiocyanate and cesium chloride gradients. Total RNA (10 mg per sample) from tumor tissue were size fractionated through 1% agarose-formaldehyde gel and transferred to nylon filters and then hybridized to 32P-labeled DNA probes and placed for autoradiography. Levels of specific RNAs were determined by computer-assisted laser densitometry. Blot filters were sequentially hybridized to nm23 and TIMP-1 probes in addition to GAPDH, as a control. Statistical analyses were carried out according to t-test for equality of means. RESULTS: NM23-H1 were detected in each sample, however it did not correlate with malignancy and invasiveness. On the other side TIMP-1 gene expression showed a clear correlation between low expression and invasiveness. CONCLUSION: The data suggest that TIMP-1 is an inhibitor of high grade gliomas invasion. NM23-H1 was present in the entire gliomas sample, but it did not vary in diffuse astrocytomas and glioblastomas. OBJETIVO: Comparar através da análise da expressão dos níveis de RNA, a presença e a relevância dos genes NM23-H1 e TIMP-1 no controle da invasão celular tumoral dentro do tecido cerebral normal em: astrocitoma difuso (OMS II) e glioblastoma multiforme (OMS:IV). MÉTODO: Análise em "Northern blot" dos genes NM23-H1 e TIMP-1. Oito astrocitomas fibrilares difusos (OMS II) e 19 glioblastomas multiformes foram analisados para determinar se TIMP-1 e NM23-H1 estavam relacinados à inibição da invasão tumoral nas neoplasias do sistema nervoso central, quantificando os níveis de RNA dos respectivos genes extraídos diretamente dos tumores. 10 mg por amostra de RNA total foram fracionados de gel de formaldeído e transferidos para os filmes de hibridação. Níveis específicos de RNAs foram determinados na espectrofotometria. Valores das razões entre NM23-H1/GAPDH e TIMP-1/GAPDH foram submetidos à análise de variabilidade das médias. RESULTADOS: A análise da expressão do gene TIMP-1 mostrou supressão em tumores gliais malignos. CONCLUSÃO: Os resultados indicam que existe relação direta entre níveis baixos de TIMP-1 e malignidade dos gliomas. O gene NM23-H1 foi detectado em todas as amostras, mas não foi possível relacionar sua subexpressão ou superexpressão com algum fenótipo de invasividade.